Peripheral Corticotropin-Releasing Factor Triggers Jejunal Mast Cell Activation and Abdominal Pain in Patients With Diarrhea-Predominant Irritable Bowel Syndrome. (27th December 2020) - Guilarte, Mar; Vicario, María; Martínez, Cristina; de Torres, Inés; Lobo, Beatriz; Pigrau, Marc; González-Castro, Ana; Rodiño-Janeiro, Bruno K.; Salvo-Romero, Eloísa; Fortea, Marina; Pardo-Camacho, Cristina; Antolín, María; et al.
Abstract : INTRODUCTION: To determine the effect of peripheral CRF on intestinal barrier function in diarrhea-predominant IBS (IBS-D). Irritable bowel syndrome (IBS) pathophysiology has been linked to life stress, epithelial barrier dysfunction, and mast cell activation. Corticotropin-releasing factor (CRF) is a major mediator of stress responses in the gastrointestinal tract, yet its role on IBS mucosal function remains largely unknown. METHODS: Intestinal response to sequential i.v. 5-mL saline solution (placebo) and CRF (100 μg) was evaluated in 21 IBS-D and 17 healthy subjects (HSs). A 20-cm jejunal segment was perfused with an isosmotic solution and effluents collected at baseline, 30 minutes after placebo, and 60 minutes after CRF. We measured water flux, albumin output, tryptase release, stress hormones, cardiovascular and psychological responses, and abdominal pain. A jejunal biopsy was obtained for CRF receptor expression assessment. RESULTS: Water flux did not change after placebo in IBS-D and HS but significantly increased after CRF in IBS-D ( P = 0.007). Basal luminal output of albumin was higher in IBS-D and increased further after CRF in IBS-D ( P = 0.042). Basal jejunal tryptase release was higher in IBS-D, and CRF significantly increased it in both groups ( P = 0.004), the response being higher in IBS-D than in HS ( P = 0.0023). Abdominal pain worsened only in IBS-D after CRF and correlated with jejunal tryptase release, water flux, and albumin output. IBS-D displayed jejunal up-regulation of CRF2 and down-regulation of CRF1 compared with HS. DISCUSSION: Stress via CRF-driven mast cell activation seems to be relevant in the pathophysiology of IBS-D.